Osteoporosis - Marcus, Robert; Feldman, David; Kelsey, Jennifer (Academic Press, 2001)
Osteoporosis is the most comprehensive, authoritative reference on this disease. Some of the topics covered include basic biology, anatomy, physiology, pathophysiology, preclinical issues, experimental medicine, management, and therapeutics. Written by renowned experts in this field, this book is a must-have for the researcher, the academic clinician, or anyone in the field of bone biology. Key Features* The source on osteoporosis* Written by expert investigators in their respective fields* Each chapter provides timely, comprehensive, and scholarly discussion* Fully illustrated in color and black & white* Covers everything from basic anatomy and physiology to diagnosis, management and treatment
Keywords: vnitřní lékařství; Minerals; Osteoporosis; Estrogen Replacement Therapy; minerály; estrogenní substituční terapie; kosti a kostní tkáň; muskuloskeletální nemoci; Bone Diseases, Metabolic; Musculoskeletal Diseases; metabolické nemoci kostí; Bone Demineralization, Pathologic; Bone and Bones; patologická demineralizace kostí; ortopedie; osteoporóza